A new synthesis of substituted benzaldehyde N-(E)-phenylmethylidenehydrazones - Obreza, Aleš (Acta chimica slovenica, 2002)
Reaction of substituted tert-butyl 2-(phenylmethylidene)-1-hydrazinecarboxylates with gaseous HCl in various anhydrous solvents affords benzaldehyde N-(phenylmethylidene)-hydrazones in very good yields. A series of substituted benzaldehydes was used for the preparation of this type of compounds. The structure of the resulting compounds was investigated by 1H-NMR, IR and MS spectra.
Keywords: analiza; hidrazinkarboskilati; hidrazoni; sinteza